1998
DOI: 10.1086/514621
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Interactions of Antibiotics Alone and in Combination

Abstract: Clinical trials show that the area under the inhibitory curve (AUIC) is predictive of antibacterial killing rates in patients with nosocomial pneumonia and is useful for predicting clinical or microbiological outcomes and making dosage adjustments with beta-lactams, quinolones, aminoglycosides, and vancomycin. The AUIC values of two antibiotics are additive, and since antibiotics are often given in combination, determining the AUIC for antibiotic combinations could potentially predict the microbiological outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…In our trial, the overall resolution of the febrile episode was observed in 92% of cases in both groups, similar to other studies [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our trial, the overall resolution of the febrile episode was observed in 92% of cases in both groups, similar to other studies [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…However, lower doses of both antibiotics have been used in some studies [4,9,21,22]. When a combination of agents is used, it is plausible that lower dosing can be administered [23]. In this scenario, the decreased dosage affords the same antibacterial activity and reduces toxicity and pharmacy costs.…”
Section: Introductionmentioning
confidence: 99%
“…However, most patients with AUIC values <125 had T>MIC of <100% and did fail (Table 7). Consequently, dosing at a T>MIC of 100% would be a minimal requirement for optimising therapy [15,[25][26][27] as well as providing protection from the emergence of resistance [28].…”
Section: Discussionmentioning
confidence: 99%
“…Since some clinicians have proposed that the concentrations of cephalosporins in serum only need to exceed the MIC 90 for 40% of the dosage interval, once-a-day administration of the doses in Tables 3 and 4 may be feasible (5). Furthermore, if combination antibiotic therapy is initiated or subsequently added, the desired clinical outcomes may be achieved with an even lower percentage of time above MIC for the cephalosporin (22).…”
Section: Discussionmentioning
confidence: 99%